Effect of kaolin addition on the performance of controlled low-strength material using industrial waste incineration bottom ash - Naganathan, S.; Razak, H.A.; Hamid, S.N.A. (2010)
Incineration of industrial waste produces large quantities of bottom ash which are normally sent to secured landfill, but is not a sustainable solution. Use of bottom ash in engineering applications will contribute to sustainability and generate revenue. One way of using the industrial waste incineration bottom ash is in controlled low-strength material (CLSM). Use of bottom ash in CLSM has problems related to bleeding and excessive strength development and so an additive has to be used to control bleeding and strength development. The main objective of this research is to study the effect of kaolin addition on the performance of CLSM made using industrial waste incineration bottom ash. CLSM mixes were made with bottom ash, cement, and refined kaolin. Various tests were performed on the CLSM in fresh and hardened states including compressive strength, water absorption, California bearing ratio (CBR) and the tests for concentration of leachable substances on the bleed and leachate. The compressive strength of CLSM tested ranged from 0.11 to 9.86 MPa. CBR values ranged from 6 to 46, and water absorption values from 12 to 36. It was shown that the addition of kaolin delayed the initial setting time of CLSM mixtures, reduced bleeding, lowered the compressive strength, and increased the values of water absorption, sorption, and initial surface absorption. The CLSM tested did not have corrosivity. It was shown that the hardened CLSM was non hazardous, and the addition of kaolin increased the concentration of heavy metals and salts in the bleed and leachate.